THE INFLUENCE OF JOB SATISFACTION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE - Widya Wati; Iskandar Ali Alam (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2026)
PURPOSE - This study aims to analyze the influence of job satisfaction and work discipline on employee performance at Citra Oleh-Oleh Bandar Lampung.METHODOLOGY - This study uses a quantitative approach with a causal associative research design. The population in this study were all 33 employees of Citra Oleh-Oleh Bandar Lampung, with a sampling technique using saturated sampling. Data were collected through a questionnaire with a Likert scale and analyzed using multiple linear regression analysis with the help of the SPSS program.FINDING - The results of the study indicate that job satisfaction has a positive and significant effect on employee performance, work discipline has a positive and significant effect on employee performance, and job satisfaction and work discipline simultaneously have a positive and significant effect on employee performance at Citra Oleh-Oleh Bandar Lampung. These findings indicate that increasing employee job satisfaction and work discipline can encourage optimal performance improvement. Therefore, companies are advised to continue to pay attention to aspects of job satisfaction and the consistent implementation of work discipline to improve employee performance and support the achievement of company goal.